2021
DOI: 10.1089/cell.2020.0087
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Adenosine Receptors in Neurological Diseases

Abstract: Adenosine plays a significant role in neurotransmission process by controlling the blood pressure, while adenosine triphosphate (ATP) acts as a neuromodulator and neurotransmitter and by activation of P2 receptors, regulates the contractility of the heart. Adenosine signaling is essential in the process of regeneration by regulating proliferation, differentiation, and apoptosis of stem cells. In this review, we have selected neurological disorders (Alzheimer's disease, Parkinson's disease, amyotrophic lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 136 publications
(146 reference statements)
0
21
0
Order By: Relevance
“…The functional roles of A 1 R and A 2A R in many neurodegenerative diseases (including AD, HD, ALS, and PD) have been extensively investigated throughout the past two decades. The current progress has been summarized and discussed in detail in recent reviews [ 15 , 91 , 157 ] and thus is not elaborated here. Previously, A 2B R and A 3 R were believed to exert only minor effects in the brain due to their low levels of expression and relatively low affinities for adenosine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional roles of A 1 R and A 2A R in many neurodegenerative diseases (including AD, HD, ALS, and PD) have been extensively investigated throughout the past two decades. The current progress has been summarized and discussed in detail in recent reviews [ 15 , 91 , 157 ] and thus is not elaborated here. Previously, A 2B R and A 3 R were believed to exert only minor effects in the brain due to their low levels of expression and relatively low affinities for adenosine.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the beneficial effects of small molecules targeting adenosine receptors seem moderate and may be effective only in specific treatment windows [ 187 ]. Because recent progress on this topic has been extensively reviewed [ 15 , 74 ], no further elaboration on the function and regulation of adenosine receptors in AD is presented here.…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine is a competitive nonselective P1 receptor antagonist binding to the A1 receptor as well as the A2A receptor [23]. Contrary to A1 receptors, the action of A2A receptors results in activation of adenylate cyclase further causing an increase in glutamatergic transmission [34]. Accordingly, the answer to the question of the effects of caffeine on the development of seizure activity is not simple.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that caffeine may cause neuronal hyperexcitability by increasing Ca 2 influx, changing potassium currents and antagonism of inhibitory A1 adenosine receptors [23,34,35]. In fact, caffeine was previously proposed as an animal model of seizures [36].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous efforts of several scientists around the world, working in the purinergic field, point to a role of A 2A receptor antagonists in the therapy of different neurological ailments [88,[120][121][122]. Specifically, clinical studies led to the development of the new firstin-class drug istradefylline, Nourias and Nourianz, in Japan and the US, respectively, for the treatment of Parkinson's disease [98].…”
Section: A 2a Adenosine Receptor As a Possible Therapeutic Target In Admentioning
confidence: 99%